2023
DOI: 10.1177/14644207231169456
|View full text |Cite
|
Sign up to set email alerts
|

A microscale constitutive model for thin stainless steel sheets considering size effect

Abstract: This research is focused on the modeling of the deformation behavior of thin austenitic stainless steel sheets to consider size effect in microscale. First, the material with two different thicknesses is heat treated to obtain different grain sizes, and then they are characterized by the uniaxial tensile tests. The experimental results show that flow stress decreases with the reduction of the sheet thickness and the increase of the grain size. The decline of the flow stress curve is associated with the decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Gau et al [17] studied the effect of size on the mechanical properties of aluminum alloy and brass, and found that the yield strength and tensile strength of the sample were reduced with decreases in thickness and increases in average grain diameter. Recently, Firouzjaei et al [18] proposed a new constitutive model based on the Swift equation to take into account the geometry and grain size effect. The proposed constitutive model can provide a good description of the flow stress by considering the interactive effect of specimen and grain sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Gau et al [17] studied the effect of size on the mechanical properties of aluminum alloy and brass, and found that the yield strength and tensile strength of the sample were reduced with decreases in thickness and increases in average grain diameter. Recently, Firouzjaei et al [18] proposed a new constitutive model based on the Swift equation to take into account the geometry and grain size effect. The proposed constitutive model can provide a good description of the flow stress by considering the interactive effect of specimen and grain sizes.…”
Section: Introductionmentioning
confidence: 99%